Biosynthesized silver nanoparticles enhanced wheat resistance to Bipolaris sorokiniana - Saima Bibi; Mubashar Raza; Muhammad Shahbaz; Maryam Ajmal; Asma Mehak; Noor Fatima; Fozia Abasi; Jaya Seelan Sathiya Seelan; Naveed Iqbal Raja; Bai Yongchao; Muhammad Zain; Rana Arsalan Javaid; et al. (Elsevier Masson SAS, 2023)
Agronomic crops can benefit from the application of nanoscale materials in order to control phytopathogens and improve plant growth. Bipolaris sorokiniana, a soil- and seed-borne fungus, causes severe yield losses in wheat. In order to determine the physio-chemical changes in wheat under biotic stress of B. sorokiniana, the current study aimed to synthesis silver nanoparticles (AgNPs) using Allium sativum bulb extract. Herein, we applied the silver nanoparticles (AgNPs) as a foliar spray on two wheat varieties (Pakistan–2013, and NARC–2011) at the concentrations of 10, 20, 30, and 40 mg/L to suppress B. sorokiniana. Among all the applied concentrations of AgNPs, the 40 mg/L concentration demonstrated the most effective outcome in reduction of the intensity of spot blotch and improved the morphological, physiological, biochemical parameters, as well as antioxidant activity in wheat plant. Foliar application of AgNPs at 40 mg/L Pakistan-2013 and NARC-2011 wheat varieties significantly increased chlorophyll a 84.8% and 53.4%, chlorophyll b 28.9% and 84.3%, total chlorophyll content 294.3% and 241.2%, membrane stability index 7.5% and 6.1%, relative water contents 25.4% and 10.5%, proline content 320.5% and 609.9%, and soluble sugar content 120% and 259.4%, respectively, compared to control and diseased plant. This is the first study provides important insights into the role of phyto-mediated AgNPs in increasing resistant of wheat infected with B. sorokiniana. These findings offers valuable new insights that may be useful for reducing disease incidence in wheat fields.